Effect of Forming Gas Furnace Annealing on the Ferroelectricity and Wake-Up Effect of Hf0.5Zr0.5O2 Thin Films. (24th January 2020) - Shekhawat, Aniruddh; Walters, Glen; Chung, Ching-Chang; Garcia, Roberto; Liu, Yang; Jones, Jacob; Nishida, Toshikazu; Moghaddam, Saeed
Abstract : The effect of furnace annealing on the ferroelectricity, leakage current, and wake-up effect in Hf0.5 Zr0.5 O2 (HZO) ultrathin film is studied as a function of furnace annealing temperature and gas environment after crystallizing the films with rapid thermal annealing in the presence of a TiN capping electrode. HZO films are deposited using atomic layer deposition in a Ge-HZO-TiN stack with Pt as the top contact electrode. The increment in the remanent polarization (Pr ) is higher when the films are furnace annealed in the forming gas ambient. Forming gas furnace annealed films show an order of magnitude less leakage current as compared to the nitrogen annealed films. Dynamic hysteresis current measurements of the HZO ultrathin films show a faster merging of the four switching peaks after cycling the virgin forming gas furnace annealed films. H-incorporation during forming gas furnace annealing does not degrade the ferroelectric properties of HZO ultrathin films unlike conventional ferroelectrics, such as PZT or SBT. Higher Pr, lower leakage current, and an improved wake-up effect of the HZO ultrathin films show its resistance to degradation by forming gas furnace annealing, which makes ferroelectric HfO2 an ideal material for next-generation ferroelectric memory devices.